Zinner Syndrome Presenting With Chronic Pelvic Pain and Ejaculatory Dysfunction - Tejasvi Patil; Amogh Verma; Rajat Sachdeva; Shubham Kumar; Shilpa Gaidhane; Sanjit Sah; Prakasini Satapathy; Rachana Mehta; Benjamin Wafula Simiyu; Vinay Suresh (IJU Case Reports)
ABSTRACT Introduction Zinner Syndrome is a rare congenital anomaly involving unilateral renal agenesis, ipsilateral seminal vesicle cyst, and ejaculatory duct obstruction. We report a symptomatic case managed conservatively. Case Presentation A 19‐year‐old male presented with 6 months of intermittent pelvic pain, dysuria, and ejaculatory discomfort. Examination was unremarkable. Ultrasonography showed right renal agenesis and a pelvic cyst. MRI confirmed a 2.8 cm cystic dilatation of the right seminal vesicle with vas deferens dilatation and absent right kidney. No ectopic renal tissue was seen. Semen analysis revealed oligospermia. Given mild symptoms and fertility concerns, he was treated conservatively with NSAIDs and antibiotics, resulting in symptom improvement within 4 weeks. Surveillance was planned. Conclusion Zinner Syndrome should be considered in young males with unexplained pelvic or ejaculatory symptoms. MRI is essential for accurate diagnosis. Conservative treatment is suitable for mild cases, reserving surgery for progressive symptoms or fertility issues.